Geoelectric Hazard Maps for the Pacific Northwest. Issue 8 (29th August 2018) - Love, Jeffrey J.; Lucas, Greg M.; Kelbert, Anna; Bedrosian, Paul A.
Abstract: Maps of extreme value, horizontal component geoelectric field amplitude are constructed for the Pacific Northwest United States (and parts of neighboring Canada). Multidecade long geoelectric field time series are calculated by convolving Earth surface impedance tensors from 71 discrete magnetotelluric survey sites across the region with historical 1‐min (2‐min Nyquist) geomagnetic variation time series obtained from two nearby observatories. After fitting statistical models to 1‐min geoelectric amplitudes realized during magnetic storms, extrapolations are made to estimate threshold amplitudes that are only exceeded, on average, once per century. One hundred‐year geoelectric exceedance amplitudes range from 0.06 V/km at a survey site in western Washington State to 9.47 V/km at a site in southeast British Columbia; 100‐year geoelectric exceedance amplitudes equal 7.10 V/km at a site north of Seattle and 2.28 V/km at a site north of Portland. Systematic and random errors are estimated to be less than 20%, much less than site‐to‐site differences in geoelectric amplitude that arise from site‐to‐site differences in surface impedance. Maps of 100‐year exceedance amplitudes are compared with the peak geoelectric amplitudes realized during the March 1989 magnetic superstorm; it is noted that some storms of relatively modest intensity can generate localized geoelectric fields of relatively high amplitude. The geography of geoelectric hazard across the Pacific Northwest is closely related to known geologic and tectonic structures. Key Points: One hundred‐year geoelectric amplitudes, estimated at discrete sites, range from 0.07 to 11.38 V/km. Geoelectric hazards show significant geographic granularity. The geography of geoelectric hazards is closely related to geologic and tectonic structures.